Physical qualities of modern pentathlon athletes in training at altitude - Wang, X.; Lian, B. (Revista Brasileira de Medicina do Esporte, 2023)
Introduction: Modern pentathlon has high requirements for the physical, psychological, and tactical training of athletes, and practicing the five items as a whole in physical training is a problem that needs to be solved. Organizing the load of each item and the overall load may be a circumventable problem using the altitude training technique. Objective: This study aimed to test and evaluate the effects of altitude training on modern pentathletes` athletic performance and functional status. At the same time, we analyzed the method`s influence on the athletes` physical quality. The ultimate goal of this experiment is to improve the science of modern pentathlete training. Methods: Six athletes from the modern pentathlon team were selected as research subjects. Changes in physiological indicators of the test subjects before and after altitude training were recorded. Mathematical statistics were used to analyze the collected data. Results: The athletes` hemoglobin during high-altitude training was significantly higher than before training (P<0.05). Other physiological indicators such as blood urea and high-density protein were not significantly different (P>0.05). Modern pentathlon performance of athletes after altitude training was significantly improved (P<0.05). Conclusion: Altitude training can improve the performance of modern pentathlon athletes. At the same time, this training method can also improve the athletes` aerobic capacity.